An Analysis of Factors Influencing Vocational Graduates’ Decision to Pursue Higher Education in Computer and Informatics Engineering - Silvia Gina Rahayu Alvi; Resmi Darni; Yeka Hendriyani; Legiman Slamet (Universitas Negeri Padang, 2025)
In the context of global competition and rapid technological advancement, vocational education plays a critical role in preparing students for direct entry into the workforce. Nevertheless, a growing number of vocational graduates are choosing to pursue higher education as a means to expand their career opportunities and social mobility. This study investigates the factors influencing such decisions, focusing on students from the Computer and Informatics Engineering Department at a vocational school in Indonesia. Using a mixed-methods design, quantitative data were gathered through structured questionnaires administered to 12th-grade students, while qualitative insights were obtained via in-depth interviews. The analysis reveals that Better Career Opportunities, Family Support, and Social Environment all have a statistically significant effect on students’ decisions to pursue tertiary education. Among these, Social Environment emerged as the most influential factor, accounting for 32.4% of the variance, followed by Family Support (3.1%) and Career Opportunities (3.1%). These findings underscore the importance of peer influence, school climate, and familial encouragement in shaping educational aspirations beyond vocational training. The results contribute to a deeper understanding of post-secondary transition dynamics in vocational contexts and provide implications for policy and practice aimed at supporting students' academic advancement.